Needs analysis of English learning in an eastern Indonesian junior high school: A study in NTT - Yeni Savitri; Thedy Hardi Manafe; Refka Darmayanthi Putri Mahisa; Dwiyani Pratiwi (Universitas Islam Negeri Ar-Raniry, 2026)
The absence of tailored English instructional materials for beginner learners in underserved regions may impede students' linguistic development. This study addresses this gap by identifying the specific learning needs of junior high school students in Kupang, East Nusa Tenggara (NTT), Indonesia. Employing an explanatory sequential mixed-methods design, data were collected from 27 purposively selected students at a public school in Kupang through online surveys and focus group interviews. Quantitative data were analyzed using frequency distribution, while qualitative data were subjected to thematic analysis. The quantitative findings revealed that 66.7% of students prioritized the development of speaking skills, despite persistent difficulties attributed to limited vocabulary knowledge. Additionally, 63% of respondents expressed a preference for technology-mediated English instruction. Thematic analysis of qualitative data generated five key themes: the need for oral communication competence, vocabulary constraints, preference for ICT-integrated learning, extrinsic motivational orientation, and the perceived value of audiovisual resources. In conclusion, English curriculum development and instructional material design for junior high school students in eastern Indonesia—particularly in NTT—should prioritize the reinforcement of communicative competence through systematic vocabulary and pronunciation instruction, complemented by the strategic integration of information and communication technology (ICT).